Physiatry Reviews for Evidence in Practice (PREP), Second-Order Peer Reviews of Clinically Relevant Articles for the Physiatrist. (October 2015) - Kumbhare, Dinesh; Robinson, Lawrence
<x xml:space="preserve">Abstract</x> ABSTRACT The busy clinically active physiatrist who wishes to practice evidence-based medicine has a daunting challenge to keep up to date with the significant amount of new information that is developing and available across the wide spectrum of medical literature. Accordingly, the authors have developed a method to survey the applicable medical literature to identify pertinent and clinically relevant articles. These articles are then critically appraised and presented in a standard format with clinically applicable conclusions. The authors will be presenting these reviews in future issues of the American Journal of Physical Medicine & Rehabilitation.